The best of Bublé [compact disc] - Bublé, Michael (Reprise Records, 2024)
An essential collection of the unmistakable voice of Michael Bublé, featuring his career-defining songs available on CD. Includes Haven't Met You Yet; Feeling Good; Sway and more, as well as two new never-released songs, Don't Blame It On Me and Quizas, Quizas, Quizas.